(untitled) (Bangladesh Journal of Medical Science, 2012)
A patient at her 38+ wks of pregnancy as a ultrasonographically diagnosed case of conjoined twin admitted in our department with ruptured membrane. Two live female babies joined at the chest were delivered by caesarean section. The parents refused a separation operation and the mother and the babies were discharged from hospital at 6th post natal day. A review of the literature suggests that early diagnosis by a combination of ultrasound and MRI is essential for management as it provides prognosis for viability and process of surgical separation and also the opportunity for early counseling of parents and termination if indicated. Key world: Conjoined twins; thoracopagus; prenatal diagnosis; separation procedure DOI: http://dx.doi.org/10.3329/bjms.v10i4.9504 BJMS 2011; 10 (4): 289-292